Legal practice in a media context - Luis Gonzalo Rodríguez López (Corporación Universitaria Minuto de Dios, 2008)
At first, this article draws attention to the need to take a stance from which to take the pedagogy of language, that with the intention of having sufficient clarity of command discipline, on the one hand and, secondly, because the fundamental role that in the formation processes of individuals, from abstraction, conceptualization and representation of reality. In a second stage, the text invites to review the practices of reading and writing, as correlates of language, focusing exclusively on the verbal, to make room for new forms which, from the media, recognize the environment today's students , faced with a new model based on digital communications.